PERAN BADAN PERMUSYAWARATAN DESA DALAM LEMBAGA PEMERINTAHAN DESA MENURUT PERATURAN MENTERI DALAM NEGERI NOMOR 110 TAHUN 2016 (STUDI KASUS DESA WAE CODI KECAMATAN CIBAL BARAT, KABUPATEN MANGGARAI) - Adrianus Uwang; Sukadi; I Wayan Kertih (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2022)
This research was conducted in Wae Codi Village, West Cibal District, Manggarai Regency, East Nusa Tenggara Province. The purpose of this study was to determine the role of the Village Consultative Body in Wae Codi Village, West Cibal District, Manggarai Regency. The type of research used in this study is a descriptive approach with data collection techniques through observation, interviews and study documentation. The results of the research carried out show that the role of the Village Consultative Body in the Village Government institution in Wae Codi Village, West Cibal District, Manggarai Regency has not run optimally according to the applicable laws and regulations. In this case, the legal basis used by the researcher refers to the Regulation of the Minister of Home Affairs Number 110 of 2016 concerning the Village Consultative Body. Through the facts found by researchers in the field related to the role of BPD in Wae Codi Village, it has not run optimally with several obstacles hampering BPD performance, namely (1) Facilities and infrastructure; (2) BPD members who do not understand the function; (3) The community does not understand the scope of the BPD; and (4) There is no socialization from the government regarding the existence of BPD in Village Government institutions.